Recent Evidence Examining Efficacy and Safety of Aspirin for Primary Cardiovascular Disease Prevention. Issue 7 (July 2019) - Carson, Erin; Hemenway, Alice N.
Background: Data on aspirin for primary prevention of cardiovascular disease (CVD) are conflicting and changing as new trials are published on the subject.Objective: To review recent data evaluating the efficacy and safety of aspirin for primary prevention of CVD.Data Sources: Articles evaluating aspirin for primary prevention of CVD were gathered using a MEDLINE search with the keywords aspirin review, aspirin peripheral artery disease, aspirin stroke, aspirin coronary artery disease, aspirin diabetes, aspirin primary prophylaxis, and aspirin elderly . Primary literature published from January 2008 through November 2018 was reviewed. Additional references were identified from a review of citations.Study Selection and Data Extraction: Randomized clinical trials that reported on aspirin for primary CVD prevention were included. In all, 10 publications met the inclusion criteria. The authors individually compared and contrasted the results from each publication.Data Synthesis: The evidence for primary CVD prevention using aspirin varies widely. Previous analyses identified a benefit to aspirin use in certain populations, and current guidelines reflect this. However, new studies published in the past 10 years call the historically identified benefit of aspirin into question and force us to reexamine which patients, if any, are indicated for aspirin for primary prevention of CVD.Relevance to Patient Care and Clinical Practice: This review provides a thorough discussion on the evidence behind aspirin for primary prevention of CVD.Conclusion: Based on current evidence, aspirin is not recommended for primary prevention of CVD.